Editorial. Accounting Academia in Central and Eastern Europe - Catalin Nicolae Albu; Nadia Albu; Belverd E. Needles (Journal of Accounting and Management Information Systems (JAMIS), 2015)
This special issue of the journal of Accounting and Management Information Systems is aimed at facilitating a deeper understanding of the changes which have occurred in accounting academia in the countries of Central and Eastern Europe (CEE), with a regional perspective in mind. The aim of this editorial is to give an overview of the papers included in the special issue.
Keywords: M41; 650; accounting academia; CEE countries; accounting education and research; academic evaluation